mestizaje, marriage and honor in Guanajuato City in 1778. An Approach to its Socio-Demographic Structure (Tzintzun, Revista de Estudios Históricos, 2016)
In the present paper we analyze the mestizaje and inter-ethnic relationsthat arose throughout colonial New Spain, through marriagesthat took place in the city of Guanajuato in 1778. We also examine themechanisms and criteria used by the Spanish Crown to identify anddiferentiate the inhabitants of New Spain. he structure of this articlecan be broken down to three analytical sections: geographical-social,social (covering some of the dynamics of coexistence in this city, suchas marriage) and the question of honor as a constraint to the mestizaje,at least in the groups with a high economic status.
Keywords: racial mixture; marriage; honor; ethnic relations; illegitimacy